ASSA14-03-31 CREG modulates Angiotensin II type 1 receptor to antagonise coronary oxidative stress and hypertension in salt-sensitive rats. (1st December 2014) - Zhang, Y; Zhao, X; Yan, C; Liu, S; Zhu, N; Zhang, X; Zhu, Z; Han, Y
Abstract : Background: This study examined whether CREG protected Sprague-Dawley (SD) rats against high salt-related hypertension and vascular endothelium oxidative stress, and explored the mechanisms and associated changes in components of the renin-angiotensin system and coronary artery injury. Methods: In this study, SD rats received pure drinking water, or drinking water containing 1.5% NaCl for 16 weeks. Systolic blood pressure was measured before rats were divided into salt-sensitive and salt-resistant groups. After 16 weeks of treatment, NO, malondialdehyde (MDA), angiotensin II and IL-6 in plasma and angiotensin II in coronary arteries were detected, as was the expression of eNOS, AT1R, AT2R and CREG. Primary lung vascular endothelial cells were incubated in culture medium containing aldosterone (0.45 nmol/l). Salt-induced changes in eNOS and activation of NAD(P)H oxidase-gp91 were assessed. Supernatant ONOO- and NO, and the expression of AT1R, AT2R and CREG were measured. Losartan was used to block AT1R effects, and to investigate the biofunction of CREG on endothelial cells. Results: The results showed that a long-term high salt intake significantly increased plasma IL-6 and MDA, angiotensin II in coronary arteries and AT1R expression, but decreased plasma NO, angiotensin II, AT2R and CREG expression in coronary arteries of salt-sensitive rats, which was prior to increase of blood pressure. Conversely, no obvious oxidative stress or vascular remodelling was observed in the salt-resistance group accompanying anti-hypertension. Mechanically, sodium concentrations significantly increased the expression of gp91 (a marker of oxidative stress) and AT1R, and reduced expression of eNOS and CREG in primary lung vascular endothelial cells from salt-sensitive rats. These effects were abrogated in cells with overexpression of CREG. Furthermore, Losartan blocking the biofunction of AT1R antagonised the NaCl-induced oxidative stress in CREG-silencing endothelial cells. Conclusions: This is the first study to identify CREG-modulated AT1R activation as a novel target to block oxidative stress in blood vessels and prevent salt-related hypertension.